2007
DOI: 10.2353/jmoldx.2007.060198
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Duplication of a Region of Chromosome Yp Encoding AMELY, PRKY, and TBL1Y

Abstract: Amelogenin has chromosome X (AMELX) and Y (AMELY) homologs that can be differentiated based on the length of polymerase chain reaction (PCR) amplification products. In addition to being useful for gender identification, analysis of amelogenin has utility for monitoring bone marrow engraftment in patients after a sex-mismatched bone marrow transplant, characterizing sex chromosome abnormalities, and for forensic purposes for analyzing mixtures of male and female DNA. Here, we describe two brothers in which PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Since duplication and deletion of the AMELY/TBL1Y (Santos et al 1998 ; Murphy et al 2007 ), TSPY (Oakey and Tyler-Smith 1990 ; Mathias et al 1994 ; Repping et al 2006 ) and the Yq region containing the CDY, BPY2 and DAZ genes (Jobling et al 1996 ; Repping et al 2003 , 2004 , 2006 ; Fernandes et al 2004 ) have been extensively documented in the literature, and can have subtle biological consequences (Repping et al 2003 ; Machev et al 2004 ; Giachini et al 2009 ), we focus here on the remaining UTY , RBMY and PRY genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since duplication and deletion of the AMELY/TBL1Y (Santos et al 1998 ; Murphy et al 2007 ), TSPY (Oakey and Tyler-Smith 1990 ; Mathias et al 1994 ; Repping et al 2006 ) and the Yq region containing the CDY, BPY2 and DAZ genes (Jobling et al 1996 ; Repping et al 2003 , 2004 , 2006 ; Fernandes et al 2004 ) have been extensively documented in the literature, and can have subtle biological consequences (Repping et al 2003 ; Machev et al 2004 ; Giachini et al 2009 ), we focus here on the remaining UTY , RBMY and PRY genes.…”
Section: Resultsmentioning
confidence: 99%
“…Two minisatellites (Jobling et al 1998 ; Bao et al 2000 ), abundant microsatellites (Kayser et al 2004 ) and some retroposon insertions (Hammer 1994 ; Santos et al 2000 ) have been reported. Molecular studies surveying the copy number of Y-specific loci similarly discovered general population duplications and deletions of segments of the chromosome that could be hundreds of kilobases or megabases in size (Jobling et al 1996 ; Santos et al 1998 ; Saxena et al 2000 ; Bosch and Jobling 2003 ; Fernandes et al 2004 ; Repping et al 2004 ; Murphy et al 2007 ; Balaresque et al 2008 , 2009 ). Rare pathological CNVs have also been identified, including cytogenetically visible deletions associated with spermatogenetic failure (Tiepolo and Zuffardi 1976 ) and anomalies of sex determination (Disteche et al 1986 ) and three distinct cytogenetically undetectable deletions leading to spermatogenetic failure (Vogt et al 1996 ), as well as insertions causing hearing impairment (Wang et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Y chromosome bears a rich complement of ampliconic repeats [16], and these are known to sponsor many recurrent rearrangements, including examples at AZFa [14, 45], AZFb [46], AZFc [26, 42, 47-49] and Amelogenin Y [13, 15]. However, this does not mean that every rearrangement is driven by these NAHR processes.…”
Section: Discussionmentioning
confidence: 99%
“…Variability involving DYS19 can be seen against a background of the generally high degree of structural variability of the Y chromosome. Cytogenetic and molecular studies have demonstrated that many large-scale structural variants exist, including deletions [11-13], duplications [11, 12, 14, 15], and inversions [12]. Underlying this structural polymorphism is a high rate of mutation through non-allelic homologous recombination (NAHR) between very similar paralogous sequences, which are particularly frequent on the Y [16].…”
Section: Introductionmentioning
confidence: 99%
“…The PRKY gene is located approximately 0.35 Mb centromeric to AMELY . To differentiate PRKX and PRKY , we designed a PCR reaction to amplify exon 8 of the PRKX and PRKY genes, using a primer set that spans a three-base pair deletion ( Table 1 ) [ 14 ]. The PRKY amplification product is three bases shorter than the PRKX product.…”
Section: Methodsmentioning
confidence: 99%